Optical investigations and photoactive solar energy applications of new synthesized Schiff base liquid crystal derivatives - Fowzia S. Alamro (Nature Portfolio, 2021)
Abstract New homologues series of liquid crystalline materials namely, (E)-3-methoxy-4-[(p-tolylimino)methyl]phenyl 4-alkloxybenzoates (I-n), were designed and evaluated for their mesomorphic and optical behavior. The prepared series constitutes three members that differ from each other by the terminally attached alkoxy chain group, these vary between 6 and 12 carbons. A laterally OCH3 group is incorporated into the central benzene ring in meta position with respect to the ester moiety. Mesomorphic characterizations of the prepared derivatives are conducted using differential scanning-calorimetry (DSC), polarized optical-microscopy (POM). Molecular structures were elucidated by elemental analyses and NMR spectroscopy. DSC and POM investigations revealed that all the synthesized derivatives are purely nematogenic exhibiting only nematic (N) mesophase, except for the longest chain derivative (I-12) that is dimorphic possesses smectic A and N phases. Moreover, all members of the group have a wide mesomorphic range with high thermal nematic stability. A comparative study was established between the present derivative (I-6) and their previously prepared isomer. The results indicated that the location exchange of the polar compact group (CH3) influences the N mesophase stability and range. The electrical measurements revealed that all synthesized series I-n show Ohmic behaviors with effective electric resistances in the GΩ range. Under white light illumination, the effective electric conductivity for the compound I-8 is five times that obtained in dark conditions. This derivative also showed two direct optical band gaps in the UV and visible light range. In addition, I-6 has band energy gaps of values 1.07 and 2.79 eV, which are suitable for solar energy applications.